Current drugs for TB treatment - Singh, Kasha (Henry Stewart Talks, 2013)
Historical perspective, Timeframe for drug and regimen development, Current regimens, Current WHO and ATS guidelines, Treatment principles, Pathological basis of action of TB drugs, Drug profiles, Limitations of current treatment regimens & special situations, Problems with first line therapy, Brief consideration of drug resistance